Descriptive study of a clinical and educational telemedicine intervention in patients with diabetes receiving glargine 300U/ml (Toujeo) in Spain: results of the T-Coach programme - Virginia Bellido; Cristóbal Morales; Araceli Muñoz Garach; José Manuel García Almeida; Juan Luis Fernández Morera; Beatriz González Aguilera; Martín López de la Torre; Diego Bellido (BioExcel Publishing Ltd, 2023)
Background: Diabetes is one of the most prevalent chronic diseases worldwide, and innovative patient support programmes can help and inform patients about their disease and improve their quality of life. The purpose of this study was to evaluate the effect of the T-Coach programme in terms of improvement of disease knowledge, self-management and adherence to treatment in a real-world setting in Spain between July 2016 and October 2018. Methods: We analyzed data from the T-Coach programme, a telephone platform that gives support to patients with type 2 diabetes mellitus treated with insulin glargine 300 U/ml (Gla-300). Support was provided by diabetes care nurses. Patients followed their treatment and aimed to achieve fasting blood glucose targets through diabetes education. Results: A total of 479 patients were included in the programme. The mean (SD) dose of Gla-300 was 28.5 (16.3) U at baseline and 31.8 (16.1) U, 31.4 (16.4) U and 32.2 (16.3) U, respectively, at 3, 6 and 12 months. A satisfaction survey was completed by 240 (50.1%) patients, who, on average, were very highly satisfied with the programme, general assistance provided, recommendations received, and calls from nurses. Conclusions: T-Coach could be an effective tool to help patients achieve their optimal dose of Gla-300 insulin and manage their blood glucose levels. It could also act as an effective support for diabetes education.